2022
DOI: 10.4102/ajlm.v11i1.1784
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and HBeAg positivity among pregnant women in South West Uganda

Abstract: Background: Hepatitis B virus is a public health burden in Uganda, yet little is known about its epidemiology in pregnancy.Objective: This study aimed at determining the prevalence and associated risk factors of hepatitis B virus infection among pregnant women attending antenatal care at the Kyazanga Health Centre IV in Lwengo District, Uganda.Methods: This cross-sectional study was conducted from April 2021 to June 2021 and analysed qualitative data that were collected using a structured in-person questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…The prevalence of HBV infection was nearly similar to results reported in Shone, Nekemte, Bishoftu, and Felegehiwot referral hospitals 4.9%, 27 5.8%, 28 6.5%, 18 and 4.7% 29 , respectively. The result of this study was relatively high when compared to the result reported from Addis Ababa at 3.7%, 20 7.8% Southern Ethiopia, 30 Gandhi memorial hospital at 2.3%, 31 Agena health center in the Gurage zone at 4.1%, 32 Uganda at 2.1% 33 , and Rwanda 3.1%. 34 The variation might be due to the differences in cultural practices and strategies used for infection prevention and risky behavior practices.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of HBV infection was nearly similar to results reported in Shone, Nekemte, Bishoftu, and Felegehiwot referral hospitals 4.9%, 27 5.8%, 28 6.5%, 18 and 4.7% 29 , respectively. The result of this study was relatively high when compared to the result reported from Addis Ababa at 3.7%, 20 7.8% Southern Ethiopia, 30 Gandhi memorial hospital at 2.3%, 31 Agena health center in the Gurage zone at 4.1%, 32 Uganda at 2.1% 33 , and Rwanda 3.1%. 34 The variation might be due to the differences in cultural practices and strategies used for infection prevention and risky behavior practices.…”
Section: Discussioncontrasting
confidence: 54%